2024
DOI: 10.1039/d3md00601h
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Ni⋯Ni interaction in Ni(ii) complexes as potential inhibitors for the development of new anti-SARS-CoV-2 Omicron drugs

Simranjeet Singh,
Mukesh Choudhary

Abstract: In this study, two nickel(ii) coordination complexes [Ni(L)]2(1) and [Ni(L)]n(2) of a tetradentate-N2O2 donor Schiff base ligand (H2L) were synthesized, designed and characterized via spectroscopic and SC-XRD analysis, and molecular docking study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“…Based on the observation from the time-dependent UV-Vis spectra, it could be concluded that the Zn( ii ) complexes [Zn(L)(en)]ClO 4 ( 1 ) and [Zn(L) 2 ] ( 2 ) were stable in the buffer solution (pH 7.4). 44…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the observation from the time-dependent UV-Vis spectra, it could be concluded that the Zn( ii ) complexes [Zn(L)(en)]ClO 4 ( 1 ) and [Zn(L) 2 ] ( 2 ) were stable in the buffer solution (pH 7.4). 44…”
Section: Resultsmentioning
confidence: 99%
“…84–87 The values of the binding energy (Δ G ) and inhibition/dissociation constant value ( K i / K d ) were also comparable to the reported values for Schiff base metal( ii ) complexes obtained from molecular docking. 40–44,58 A structure–activity relationship (SAR) was established between the experimental geometries of the Zn( ii ) complexes [Zn(L)(en)]ClO 4 ( 1 ) and [Zn(L) 2 ] ( 2 ) determined by the single-crystal X-ray diffraction technique and the theoretical geometries observed with interactions against SARS-CoV-2 RBD protein (PDB ID: ) and Omicron S protein (PDB ID: ), as tabulated in Table S7 (ESI†). Table S8 (ESI†) shows a comparison of the docking energies (Δ G ) and inhibition/dissociation constant values ( K i / K d ) of some new metal complexes obtained from in silico docking studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations